2010
DOI: 10.1111/j.2041-1626.2010.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive periodontal disease has a simultaneous incremental elevation of gingival crevicular fluid and serum CRP levels

Abstract: C-reactive protein levels in gingival crevicular fluid and serum increased proportionately with the severity of periodontal disease. They correlated positively with clinical parameters, including gingival index, probing pocket depth, and clinical attachment level. Thus, it can be considered as a periodontal inflammatory biomarker and deserves further consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 37 publications
5
37
1
Order By: Relevance
“…The results of the present study are in accordance with those of previous study in which serum PGRN levels were elevated in diabetic subjects [17]. The increase in serum and GCF concentrations of hs-CRP from health to chronic periodontitis to chronic periodontitis with DM in the present study is in accordance with a previous study [39]. We further found significant relationship between PGRN and hs-CRP concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study are in accordance with those of previous study in which serum PGRN levels were elevated in diabetic subjects [17]. The increase in serum and GCF concentrations of hs-CRP from health to chronic periodontitis to chronic periodontitis with DM in the present study is in accordance with a previous study [39]. We further found significant relationship between PGRN and hs-CRP concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study are in accordance with that of previous study in which elevated serum PGRN levels in obese subjects were reported [20]. The increase in serum and GCF concentrations of hs-CRP in the present study are in accordance with a previous study [39]. In contrast to a previous study [40] which demonstrated almost non detectable amount of hs-CRP in GCF, we detected sufficiently large amount in GCF.…”
Section: Discussionsupporting
confidence: 92%
“…It was anticipated that such a comparison and correlation would further validate the role of the new molecule (in this case, SCF) being tested. The observed increase in hs-CRP, an acute-phase reactant protein and one of the most important markers of inflammation from Group 1 to Group 2, was in accord with a previous study by Pradeep et al in which CRP levels in GCF and serum were measured using ELISA (24), and also with a study by Noack et al (11) The mean GCF concentration of CRP in the periodontitis group was very much higher than that in the gingivitis group and healthy group. Similarly, the mean serum concentration of CRP in the periodontitis group was higher than that in the gingivitis group, which in turn was higher than that in the healthy group.…”
Section: Discussionsupporting
confidence: 91%